2018
DOI: 10.1097/tp.0000000000002057
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescription, Morbidity, and Mortality in US Transplant Recipients

Abstract: In contrast to either no or short-term OpRx, long-term, and especially long-term high-dose OpRx, is associated with increased risk of death and graft loss in US KTx recipients. Causal relationships cannot be inferred, and OpRx may be an illness marker. Nevertheless, efforts to treat pain effectively in KTx recipients with less toxic interventions and decrease OpRx deserve consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Online supplementary Table 2 shows the list of medications that we categorized as analgesics. Comorbidities ascertained from the CMS Form 2728 included congestive heart failure, peripheral vascular disease, cerebrovascular disease, current smoker status, atherosclerotic heart disease, diabetes, and AIDS [6,8]. Medicare inpatient billing data were used to identify diagnoses of…”
Section: Exposure Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Online supplementary Table 2 shows the list of medications that we categorized as analgesics. Comorbidities ascertained from the CMS Form 2728 included congestive heart failure, peripheral vascular disease, cerebrovascular disease, current smoker status, atherosclerotic heart disease, diabetes, and AIDS [6,8]. Medicare inpatient billing data were used to identify diagnoses of…”
Section: Exposure Variablesmentioning
confidence: 99%
“…Numerous studies in the end-stage renal disease (ESRD) population have shown that pain is highly prevalent and debilitating [1][2][3], associated with poor perception of quality of life [4] and increased opioid prescription rates over time [5]. We and others have shown opioid prescriptions in the ESRD population are associated with adverse health outcomes including mortality, dialysis discontinuation, hospitalizations, altered mental status, falls, and fractures, as in the general population [6][7][8]. In response to the opioid epidemic, federal regulatory agencies have mandated and implemented strategies to limit opioid use and identify alternative medications for appropriate treatment of pain [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients treated with opioids may have worse long‐term outcomes than patients not taking these drugs . In addition, high doses of opioids have been linked to worse outcomes in chronic disease patients, such as those on long‐term hemodialysis and kidney transplant recipients . In addition, Randall et al reported worse LT outcomes in association with opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Using scientific registry of transplant recipient data and by linking it to billing claims, Randal et al showed that higher dose of opioids among waitlisted patients for LT has been associated with higher 5 years post‐LT mortality compared to non‐opioid users. Long‐term prescription opioid treatment has resulted in higher incidence of allograft loss and increased mortality compared to no or short‐term treatment . Moreover, increased healthcare utilization has been reported among liver disease patients with pain and an opioid prescription; however, this assessment was performed at a single point in the natural history of cirrhosis .…”
Section: Introductionmentioning
confidence: 99%